Application of Human Induced Pluripotent Stem Cell-Derived Cellular and Organoid Models for COVID-19 Research - Luo, Yumei; Zhang, Mimi; Chen, Yapei; Chen, Yaoyong; Zhu, Detu (Frontiers in Cell and Developmental Biology, 2021)
The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its rapid international spread has caused the coronavirus disease 2019 (COVID-19) pandemics, which is a global public health crisis. Thus, there is an urgent need to establish biological models to study the pathology of SARS-CoV-2 infection, which not only involves respiratory failure, but also includes dysregulation of other organs and systems, including the brain, heart, liver, intestines, pancreas, kidneys, eyes, and so on. Cellular and organoid models derived from human induced pluripotent stem cells (iPSCs) are ideal tools for in vitro simulation of viral life cycles and drug screening to prevent the reemergence of coronavirus. These iPSC-derived models could recapitulate the functions and physiology of various human cell types and assemble the complex microenvironments similar with those in the human organs; therefore, they can improve the study efficiency of viral infection mechanisms, mimic the natural host-virus interaction, and be suited for long-term experiments. In this review, we focus on the application of in vitro iPSC-derived cellular and organoid models in COVID-19 studies.